Business Model Canvas Effect Risk Management and Business Performance: SMEs in Rayong, Thailand - BOONNUAL, CHUTIMANT; THAWORNSUJARITKUL, THITIRAT (The journal of contemporary issues in business and government, 2021)
This research studied the relationship of business operations based on business elements of Business Model Canvas that influenced the efficiency in risk management and the performance of SMEs in Rayong province. The research is based on a Quantitative research methodology, where data collection has been achieved through self- administered questionnaires. The statistical results found that the Business Model Canvas influenced SMEs performance in Rayong.The empirical data and correlation testing via Structure Equation Modeling in which found thatSMEs businesses in Rayong had well business plan that covered all the nine aspects of Business Model Canvas with the efficient risk management.Both led to the well Balance Scorecard performance including the well business plan that would lead the business to have good risk management efficiency. The risk management efficiency was the partial mediation from the Business Model Canvas to the business performance result.